Periodic Versus “Can-Order” Policies for Coordinated Multi-Item Inventory Systems - Atkins, Derek R.; Iyogun, Paul O. (Management Science, 1988)
The coordinated multi-item inventory problem refers to the problem of managing inventories where there is a joint fixed cost for replenishing plus an item-by-item fixed cost for each item included in the replenishment order. Given that the optimal solution is likely to be too complex, attention has focused on fixed heuristics, and in particular ‘can-order’ or (s, c, S) policies. This paper makes two contributions. First, a new lower bound on the cost of the optimal policy is proposed in order that the performance of heuristics may be measured. Second, motivated by the lower bound, a simple periodic policy is proposed and shown to be an improvement over ‘can-order’ policies for many data sets.